Optimizing patient care and outcomes through the congenital heart center of the 21st century. (5th February 2018) - Anderson, Jeffery B.; Chowdhury, Devyani; Connor, Jean A.; Daniels, Curt J.; Fleishman, Craig E.; Gaies, Michael; Jacobs, Jeffrey; Kugler, John; Madsen, Nicolas; Beekman, Robert H.; Lihn, Stacey; Stewart‐Huey, Kay; et al.
Abstract: Pediatric cardiovascular services are responding to the dynamic changes in the medical environment, including the business of medicine. The opportunity to advance our pediatric cardiology field through collaboration is now realized, permitting us to define meaningful quality metrics and establish national benchmarks through multicenter efforts. In March 2016, the American College of Cardiology hosted the first Adult Congenital/Pediatric Cardiology Section Congenital Heart Community Day. This was an open participation meeting for clinicians, administrators, patients/parents to propose metrics that optimize patient care and outcomes for a state‐of‐the‐art congenital heart center of the 21st century. Care center collaboration helps overcome the barrier of relative small volumes at any given program. Patients and families have become active collaborative partners with care centers in the definition of acute and longitudinal outcomes and our quality metrics. Understanding programmatic metrics that create an environment to provide outstanding congenital heart care will allow centers to improve their structure, processes and ultimately outcomes, leading to an increasing number of centers that provide excellent care. This manuscript provides background, as well listing of proposed specialty domain quality metrics for centers, and thus serves as an updated baseline for the ongoing dynamic process of optimizing care and realizing patient value.